1980
DOI: 10.1063/1.91872
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature crystallization of doped a-Si:H alloys

Abstract: Crystallization of phosphorus-doped a-Si:H has been initiated at a substrate temperature below 200 °C, under the deposition conditions of a low flow rate of silane and in the presence of an external magnetic field. Along with the crystallization, the doping efficiency of the resulting Si:H films has been remarkably improved. Room-temperature conductivity as high as 27 Ω−1 cm−1 has been achieved at a doping ratio of NPH3/NSiH4=5.6×10−3 for a specimen deposited at 30 C. Optical emission spectroscopy during the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Several techniques for low-temperature deposition of poly-Si have been intensively investigated like, e.g. magnetron sputtering [1], plasma enhanced chemical vapor deposition (PECVD) [2], hot-wire CVD (HW-CVD) [3], and photo-CVD [4]. These techniques, however, are not fully mature yet and several problems need to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques for low-temperature deposition of poly-Si have been intensively investigated like, e.g. magnetron sputtering [1], plasma enhanced chemical vapor deposition (PECVD) [2], hot-wire CVD (HW-CVD) [3], and photo-CVD [4]. These techniques, however, are not fully mature yet and several problems need to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the good conductivity of PEDOT, PSS is usually regarded as an insulator . Here, our measurements show that the PSS thin film possessed an initial value of 34 mS cm −1 , which rivals the conductivity of doped a‐Si:H thin films . It was found that the conductivity of PSS was not stable under exposure to the ambient environment and degraded from 34 to 4.5 mS cm −1 in 1 h. The mechanism of the conductivity stability is related to the hydrophilicity of the PSS thin films, and more detailed analysis is seen in the supplementary material.…”
mentioning
confidence: 66%
“…Microcrystalline silicon was first reported by Veprek and Marecek in Europe in 1968 [71], and in Japan by Matsuda et al [72] and Hamasaki et al [73] in 1980.…”
Section: Microcrystalline or Nanocrystalline Siliconmentioning
confidence: 99%